Green synthesis of AgNPs using Forsskaolea tenacissima: sustainable nanotechnology for antimicrobial, antioxidant, and catalytic activities - Alorfi, Hajer S.; Alomari, Maha S.; Bawakid, Nahed O.; Althagbi, Hanan I.; Alsebaii, Naha M.; Aslam, M.; Chandrasekaran, S.; Soomro, M. Tahir; Khan, Amna N. (Frontiers in Nanotechnology, 2025)
Antimicrobial resistance is rapidly increasing worldwide, leading to higher mortality rates, particularly among children, as improper antibiotic use renders treatments less effective. Plant-derived AgNPs have emerged as sustainable natural agents, offering enhanced antimicrobial activity against multidrug-resistant bacteria without promoting further resistance. In this context, the Urticaceae plant Forsskaolea Tenacissima (F. Tenacissima), with its rich phytochemical content and traditional medicinal uses, remains largely unexplored for green AgNP synthesis. Motivated by this gap, we investigated Ft-AgNPs as a novel antimicrobial, antioxidant, and catalytic agent. Compared to well-studied plants like Azadirachta indica and Ocimum sanctum, F. Tenacissima offers a distinct and potentially more potent phytochemical composition, making it a promising candidate for sustainable AgNPs synthesis. The synthesis was rapid and efficient, with the F. Tenacissima aqueous leaf extract serving as both reducing and stabilizing agent in the formation of Ft-AgNPs. UV-Visible spectroscopy revealed a characteristics absorption peak at 446 nm, confirming the formation of Ft-AgNPs. SEM analysis showed densely packed, spherical Ft-AgNPs, while a zeta potential of −28.1 mV indicated strong electrostatic repulsion, suggesting good colloidal stability. DLS analysis supported the size distribution observed in TEM images, and XRD confirmed the crystalline nature and face-centered cubic (fcc) structure of Ft-AgNPs. FTIR and HPLC analysis identified 4-hydroxybenzoic acid and salicylic acid in the plant extract, which played a key role in the reduction of Ag+ ions and stabilization of Ft-AgNPs. The antibacterial efficacy of Ft-AgNPs was demonstrated against B. cereus, E. coli, and P. aeruginosa using disk diffusion and serial dilution methods. For antifungal activity, two yeasts species, C. alibicans and C. glabrata, were tested. Antioxidant potential was assessed through the DPPH radical scavenging assay, while catalytic activity was evaluated via the reduction of two common wastewater pollutants, 4-nitrophenol (4-NP) and methylene blue (MB), using Ft-AgNPs and NaBH4. Overall, the study highlights the efficient green synthesis of Ft-AgNPs with remarkable antimicrobial, antioxidant, and catalytic properties, offering a sustainable and effective approach for the development of multifunctional nanomaterials.